2015
DOI: 10.1111/sms.12379
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress exacerbates the reduction in middle cerebral artery blood velocity during prolonged self‐paced exercise

Abstract: This study examined the influence of hyperthermia on middle cerebral artery mean blood velocity (MCA Vmean). Eleven cyclists undertook a 750 kJ self-paced time trial in HOT (35°C) and COOL (20°C) conditions. Exercise time was longer in HOT (56 min) compared with COOL (49 min; P < 0.001). Power output in HOT was significantly lower from 40% of work completed onward (P < 0.01). Rectal temperature increased to 39.6 ± 0.6°C (HOT) and 38.8 ± 0.5°C (COOL; P < 0.01). Skin temperature, skin blood flow, and heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…In agreement with previous observations (27,28), V O 2 and power output (Fig. 1) decreased throughout the time trials in the HOT condition, concomitant with the development of thermal (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous observations (27,28), V O 2 and power output (Fig. 1) decreased throughout the time trials in the HOT condition, concomitant with the development of thermal (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The lower power output noted at the start of the time trial in the HOT condition was somewhat atypical and may stem from subjects consciously adopting a conservative approach, knowing that four separate time trials had to be performed. Indeed, power output in the heat usually matches that of cooler conditions for the first 10 -15 min of time trials (10,27,28,30,42,46), unless participants are inexperienced at performing such tasks (40), or the self-paced effort is preloaded with exercise in the heat (9). Hettinga et al (18) also showed that cycling in the heat decreases gross efficiency by 0.9% relative to cooler conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations